2009
DOI: 10.1021/jp907822h
|View full text |Cite
|
Sign up to set email alerts
|

Chain-Breaking Activity of Carotenes in Lipid Peroxidation: A Theoretical Study

Abstract: Chain-breaking reactions against lipid peroxidation performed by carotenes, including beta-carotene (beta-CAR) and lycopene (LYC), have been studied using density functional theory. We chose linoleic acid (LAH) as the lipid model and examined two mechanisms: hydrogen abstraction and addition. Our computed reaction diagrams reveal that the addition mechanism is able to offer a larger extent of chain-breaking protection than hydrogen abstraction. In the case of hydrogen abstraction, the resulting carotene radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…More frequently, they act as direct radical scavengers of the lipid peroxidation chain reactions (chain breakers). Chain-breakers donate an electron to the free radical, neutralizing the radicals and themselves becoming stable (less reactive) radicals, thus stopping the chain reactions [43,44,45]. …”
Section: Biological Roles and Implications (Mainly On Antioxidant mentioning
confidence: 99%
“…More frequently, they act as direct radical scavengers of the lipid peroxidation chain reactions (chain breakers). Chain-breakers donate an electron to the free radical, neutralizing the radicals and themselves becoming stable (less reactive) radicals, thus stopping the chain reactions [43,44,45]. …”
Section: Biological Roles and Implications (Mainly On Antioxidant mentioning
confidence: 99%
“…The reaction of carotenoids as scavengers of both short-lived and long-lived oxidizing radicals has been investigated. In homogeneous solutions reaction pathways have been found to depend on both the nature of the reacting free radical and the structure of carotenoid [ 18 , 36 , 37 , 38 , 39 , 40 ]. Three possible mechanism, shown as the reactions of Equations (6), (7) and (8), may be involved:…”
Section: Radical Scavenging Of Flavonoids and Carotenoidsmentioning
confidence: 99%
“…51,52 We found that the chain-terminating function of CAR is attributed to the trapping of the radical and the suppression of the addition of O 2 . Furthermore, a hydrogen abstraction mechanism also contributes to the protective function of CARs, although to a lesser extent.…”
Section: → • Initiation: Rh Rmentioning
confidence: 91%